The Effect of the Dr. LEE Jong‐wook—Seoul Project on Medical Student Academic Performance in Laos - 김정호; 김태종; 신좌섭 (의학교육논단, 2019)
The Dr. LEE Jong-wook—Seoul Project (DLSP) in the Lao People’s Democratic Republic (PDR) is a long-term development cooperation initiative aimed at upgrading the medical education capacity at the University of Health Sciences (UHS) in the Lao PDR. Under the project, eight faculty members from UHS were trained at the Seoul National University College of Medicine for a 12-month period during 2010–2011. Using a training-of-trainers model, we estimated the effect of DLSP on the learning outcomes of students, which was measured using the standard test scores of the students. The questionnaire developed by the Medical Education Assessment Consortium in Korea was given to the students and both the percent-correct and standardized scores were examined. The evaluation strategy was to compare the learning outcomes of the students taught by the trainees with those that were not and to compare the medical topics taught by the trainees with other topics. It was found that the first group of trainees in the DLSP was associated with an increase of 1.5 in the percent-correct test scores for basic medicine. While the interpretation requires caution, it is consistent with the view that a training program for faculty members could be effective in improving the teaching capacity of medical schools in developing countries.
Keywords: Developing countries; Educational measurement; Teacher training